Distribution, habitats, phenology and conservation of New Caledonian Odonata - Grand, Daniel; Marinov, Milen; Jourdan, Herve; Cook, Carl; Rouys, Sophie; Mille, Christian; Theuerkauf, Jörn (Zootaxa, 2019)
Compared to other archipelagos of the Pacific, the New Caledonian Odonata fauna is rich and diverse with 56 valid species or subspecies (23 endemics, 41%) from eight families (four Zygoptera: Argiolestidae, Coenagrionidae, Isostictidae, Lestidae, and four Anisoptera: Aeshnidae, Corduliidae, Synthemistidae, Libellulidae) and 31 genera (including four endemics, 13%). In Zygoptera, we record 19 species including 12 endemics (63%), and among Anisoptera, we record 37 species or subspecies, including 11 endemics (30%). We removed five species from the list that had been erroneously recorded as occurring in New Caledonia: Tramea carolina (Linnaeus, 1763), Austroargiolestes icteromelas (Selys-Longchamps, 1862), Ischnura torresiana Tillyard, 1913, Xiphiagrion cyanomelas Selys-Longchamps, 1876 and Hemicordulia oceanica Selys-Longchamps, 1871. The occurrence of Tramea limbata (Desjardins, 1835) appears also doubtful, but we were unable to clarify to which taxon this record referred hence we excluded it from our update. From a biogeographic perspective, the New Caledonian fauna has mostly Australian affinities with some connections with southeast Asia and the Pacific region. We provide for each species, whenever information was available, a distribution map with a brief review of its known ecology, behaviour and phenology. We also evaluated each species’ conservation status, in light of known threats (range restriction, scarcity and human activity including altered water flow). We consider seventeen species (30%) endangered. The most immediate threats concern water pollution including alteration to the flow of water courses caused by mining, deforestation and fires. Invasive species, such as alien fish, may be predators of concern for odonata larva, although this has not yet been proven in New Caledonia.